2011
DOI: 10.1039/c0ob00961j
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the formation and stabilization of human telomeric G-quadruplex DNA, inhibition of telomerase and cytotoxicity by phenanthroline derivatives

Abstract: Four new di-substituted phenanthroline-based compounds a-d have been designed and prepared, and they have been shown to induce the formation of anti-parallel structure of human telomeric G-quadruplex DNA by CD spectra. FRET assay indicates that the melting temperature increases (DT m values) of G-quadruplex in buffer (pH 7.4) containing 100 mM NaCl are 31.6, 34.6, 17.8 and 32.6• C for the compounds (1.0 mM) a, b, c and d, respectively. Competitive FRET assay shows that the four compounds exhibit a high G-quadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…The melting Table 3). The T m values of the compound/i-motif complexes were lower than those of the compound/G-quadruplex complexes, in which their corresponding T m values were 32.5, 37.6 and 35.4 • C at 5 times excess of compound concentration [26]. The results suggested that three compounds are the potent stabilization agents for G-quadruplex DNA.…”
Section: Uv-melting Analysismentioning
confidence: 81%
See 4 more Smart Citations
“…The melting Table 3). The T m values of the compound/i-motif complexes were lower than those of the compound/G-quadruplex complexes, in which their corresponding T m values were 32.5, 37.6 and 35.4 • C at 5 times excess of compound concentration [26]. The results suggested that three compounds are the potent stabilization agents for G-quadruplex DNA.…”
Section: Uv-melting Analysismentioning
confidence: 81%
“…Compounds 1-3 were synthesized according to a previously reported literature [26]. Stock solutions were prepared by dissolving in DMSO at a concentration of 5 mM and kept at −20 • C. Before experiments, the concentrated compound was diluted in buffer solution.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations